THE INFLUENCE OF VIRAL MARKETING AND DIGITAL MARKETING ON CONSUMER LOYALTY WITH THE DECISION TO PURCHASE SKINTIFIC PRODUCTS AS AN INTERVENING VARIABLE - Utami , Rahmah Esti; Welsa, Henny; Hutami, Lusia Tria Hatmani (International Conference on Humanity Education and Society (ICHES), 2024)
Purchasing decisions are actions on two or more alternatives so that a person can make a decision if there are alternative choices. The literature on improving purchasing decisions still has inconsistencies such as viral marketing in several articles proven to have a positive and significant influence but other research is not proven to have a positive and significant influence on decisions. purchases. This research aims to further explore what variables have an influence on increasing purchasing decisions and adding purchasing decisions as a mediator. This research aims to determine the influence of viral marketing, digital marketing and consumer loyalty mediated by partial and simultaneous purchasing decisions. This research involved 102 respondents using scientific products with a sampling technique using non-probability purposive sampling, while data processing used SPPS 2.6. The results show that viral marketing, digital marketing and consumer loyalty have a positive and significant effect on purchasing decisions. Mediation analysis shows that purchasing decisions are able to mediate viral marketing on consumer loyalty and purchasing decisions are able to mediate digital marketing on consumer loyalty.